Small molecule fisetin modulates alpha-Synuclein aggregation - Rosado-Ramos, Rita (2021)
Funding Information: iNOVA4Health Research Unit (LISBOA-01-0145-FEDER-007344), which is co-funded by Funda??o para a Ci?ncia e Tecnologia (FCT)/Minist?rio da Ci?ncia e do Ensino Superior, through national funds, and by FEDER under the PT2020 Partnership Agreement, is acknowledged. Authors would like to acknowledge FCT for financial support of RR (SFRH/BD/116597/2016). JP, RR, GG, and CNS acknowledges funding via BacHBerry (Project No. FP7-613793; www.bachberry.eu). RM is funded by FCT Scientific Employment Stimulus Contract CEEC/04567/CBIOS/2020. TFO was supported by the DFG Center for Nanoscale Microscopy and Molecular Physiology of the Brain (CNMPB) and is currently supported by the Deutsche Forschungsgemeinschaft (DFG, German Research Foundation) under Germany?s Excellence Strategy?EXC 2067/1-390729940. It is also acknowledged the European Research Council (ERC) under the European Union?s Horizon 2020 Research and Innovation Programme under Grant Agreement No. 804229. Publisher Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland.